Age Differences in the Experience of Daily Life Events: A Study Based on the Social Goals Perspective - Ji, Lingling; Peng, Huamao; Xue, Xiaotong (Frontiers in Psychology, 2017)
This study examined age differences in daily life events related to different types of social goals based on the socioemotional selectivity theory, and determined whether the positivity effect existed in the context of social goals in older adults' daily lives. Over a course of 14 days, 49 older adults and 36 younger adults wrote about up to three life events daily and rated the valence of each event. The findings indicated that 1) although both older and younger adults recorded events related to both emotional and knowledge-acquisition goals, the odds ratio for reporting a higher number of events related to emotional goals compared to the number of events related to knowledge-acquisition goals was 2.12 times higher in older adults than that observed in younger adults. 2) Considering the number of events, there was an age-related positivity effect only for knowledge-related goals, and 3) older adults' ratings for events related to emotional and knowledge-acquisition goals were significantly more positive compared to those observed in younger adults. These findings supported the socioemotional selectivity theory, and to some extent, the positivity effect was demonstrated in the context of social goals.